PERMODELAN BANGKITAN PERGERAKAN PADA TATA GUNA LAHAN SMU NEGERI DI MAKASSAR - Syafruddin Rauf (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2009)
The location of high school is a place where traffic jam frequently occurs. Therefore, the selection of school locations should consider the trips generated by the school activities. The purpose of this study is to develop trip generation models for the school areas. Surveys were conducted at five state high school locations inMakassar city. The results show that the amount of trips to bring students to school is affected by the total school area, the number of class rooms, and the area of class rooms. Meanwhile, the amount of trips to pickup student is influenced by upon the total school area and the area of class roomsKeywords: trip generation, school activity, school area, and area of class rooms.